Immune response in feeder cattle fed different sources of dietary lipid - T.B. Farran; M.F. Spire; J.J. Sindt; Sean P. Montgomery; C.M. Coetzer; H.J. LaBrune; J. Ernest Minton; James J. Higgins; T.H. Elsasser; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2002)
Two studies were conducted utilizing crossbred beef steers to evaluate immune response following endotoxin challenge. In Trial 1 steers (n = 20; 688 lb BW) were fed diets containing rolled full-fat soybeans (SOY) or tallow (TALLOW). In Trial 2, steers (n=18; 780 lb BW) were fed diets containing TALLOW, flaxseed (FLAX), or a micro-algae (ALGAE) top-dressed to the TALLOW diet. Both FLAX and ALGAE were sources of omega-3 polyunsaturated fatty acids. In both trials, diets were fed for a 14-day acclimation period prior to intravenous injection of a bacterial lipopolysaccharide(LPS) endotoxin. Injection of LPS in Trial 1 resulted in higher rectal temperatures for animals fed TALLOW compared to those fed SOY. In contrast, plasma concentrations of tumor necrosis factor-Î± (TNF) were higher for animals fed SOY. Haptoglobin and fibrinogen increased and total white blood cell count decreased in response to LPS, but these measures were not different (P>0.1) between SOY and TALLOW. In Trial 2, rectal temperature was higher for TALLOW (P<0.05) than for FLAX at 3, 4, 5, and 6 hours after the initial injection of LPS. In addition, rectal temperature for TALLOW was higher (P=0.05) at hour 4 when compared to ALGAE and tended (P=0.1) to be higher at hour 5. Serum haptoglobin concentration at 24 hours was higher (P<0.05) for animals fed ALGAE than those fed FLAX or TALLOW. Haptoglobin and fibrinogen concentrations increased at 24 hours after injection with LPS, but were not different at other times among treatments in either trial. Results show that source and type of dietary fatty acid may impact immune response in cattle.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Endotoxin challenge; Immune modulation; Lipids